ANALISIS FAKTOR INTERNAL-EKSTERNAL TERHADAP PENGELOLAAN OBAT DI INSTALASI FARMASI RSUD DR. MOEWARDI SURAKARTA - Sholichah Rochmani; Achmad Fudholi; Lukman Hakim (Universitas Sebelas Maret, 2016)
SWOT analysis is first step for formulating the strategic, to analyze the external and internal environmental factors. The purpose of this research is to analyze the external and internal environmental factors which influence pharmacy department, formulating the strategic management of the pharmacy department that can increase good works Pharmacy Department of RSUD Dr. Moewardi Surakarta .The method for the research is realized by collecting secondary data related to drugs management in pharmacy department, and then collect the primary data by conducting direct observation in the form of interview with Chief Pharmacy Department and distribute questionnaires to the doctor, officials, and patients. To determine the management of drug using the drug management indicators and to determine strengths, weaknesses, opportunities, and threats using SWOT analysis. The result showed that the internal environmental factor such as drug management in selection phase, selected drugs by DOEN is 6%. Procurement phase, the percentage of capital available along with all the used fund can only absorbs the average of 95,6% of the real total, percentage according to between planning with the fact to inappropriate drug 105,01%, and the average availability of medicine of 35 days. On distribution phase, the expired or damaged medicine out of the supported 0%. Use phase, showed by the waiting time for outpatient uncompounding prescription is 30,47 minutes and compounding prescription is 60,01 minutes. External environmental factors in pharmacy department such as opportunity: human resources in pharmacy department need to practical training, a good service in pharmacy department, drugs is complete; threats focused on existing hospitals in Surakarta, good services for customers quality, long waiting time for drug in pharmacy department. Pharmacy Department of RSUD Dr. Moewardi Surakarta was on the first quadrant. The strategy which can be used by Pharmacy Department of RSUD Dr. Moewardi Surakarta in this condition is to support the aggressive growing policy (growth oriented strategy).